Collaborating for a Thriving Maine Forest Sector - Pugh, Katrina; Uhrig, Emily; Fergusson, Meg; Weiskittel, Aaron; Moeykens, Shane; Saffeir, Jo (Maine Policy Review, 2024)
The authors of this commentary describe a coming together of an EPSCoR planning team with community leaders across the northeastern US forest sector. The community leaders came in support of this high-stake NSF proposal and in support of each other. As a result, their transdisciplinary deliberations on data and artificial intelligence (AI), economics, inclusion, and learning not only generated inputs to the recently announced 7 million NSF EPSCoR E-RISE award (OIA-2416915), but also gave them new language to describe their collaboration capacity.